2013
DOI: 10.3892/ijmm.2013.1350
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide 1 regulates adipogenesis in 3T3-L1 preadipocytes

Abstract: Abstract. Glucagon-like peptide 1 (GLP-1), a gut-derived peptide, has been reported to have profound effects on metabolism and to reduce insulin resistance. Adipocyte hyperplasia stimulated by preadipocyte differentiation has a positive effect on adipose tissue insulin sensitivity. However, it remains less clear whether GLP-1 plays a role in adipogenesis. In this study, we examined the effect of GLP-1 on preadipocyte differentiation and investigated the mechanisms that may be involved in this effect. In our 3T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…To explore the possible roles of GLP-1/ GLP-1R in adipogenesis and lipid metabolism, we first examined the expression profile of GLP-1R in 3T3-L1 adipocytes. Consistent with previous observations [43,44], we confirmed the presence of GLP-1R in both preadipocytes and differentiated adipocytes. Interestingly, we found that GLP-1R expression in both mRNA and protein levels decrease along with the differentiation, which may imply that GLP-1/GLP-1R signaling could play more important roles in undifferentiated adipocytes.…”
Section: Discussionsupporting
confidence: 81%
“…To explore the possible roles of GLP-1/ GLP-1R in adipogenesis and lipid metabolism, we first examined the expression profile of GLP-1R in 3T3-L1 adipocytes. Consistent with previous observations [43,44], we confirmed the presence of GLP-1R in both preadipocytes and differentiated adipocytes. Interestingly, we found that GLP-1R expression in both mRNA and protein levels decrease along with the differentiation, which may imply that GLP-1/GLP-1R signaling could play more important roles in undifferentiated adipocytes.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, we also investigated the effect of GLP‐1 on Akt and ERK, intracellular signalling pathways that have been reported to be activated by GLP‐1 in adipocytes and other cell types (Challa et al ., ; Yang et al ., ). Neither Akt nor ERK1/2 phosphorylation rates were modified after 5 or 30 min of exposure of differentiated 3T3‐L1 cells to GLP‐1 (Figure S1B).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have associated ghrelin and GLP‐1 with adipogenesis. Both GI hormones stimulate adipogenesis; ghrelin acts mainly on insulin sensitivity and GLP‐1 induces adipogenesis by stimulating differentiation of and inhibiting apoptosis of preadipocytes . These data suggest that these hormones may have a cross‐talk effect on adipogenesis.…”
Section: Introductionmentioning
confidence: 88%